Cryptographic Accumulator and Its Application: A Survey. (7th March 2022) - Ren, Yongjun; Liu, Xinyu; Wu, Qiang; Wang, Ling; Zhang, Weijian
Abstract : Since the concept of cryptographic accumulators was first proposed in 1993, it has received continuous attention from researchers. The application of the cryptographic accumulator is also more extensive. This paper makes a systematic summary of the cryptographic accumulator. Firstly, descriptions and characteristics of cryptographic accumulators are given, and the one-way accumulator, collision-free accumulator, dynamic accumulator, and universal accumulator are introduced, respectively. Cryptographic accumulator can be divided into two types: symmetric accumulator and asymmetric accumulator. In the asymmetric accumulator, three different cryptographic accumulator schemes were classified based on three security assumptions. Finally, this paper summarized the applications of cryptographic accumulators in ring signature, group signature, encrypted data search, anonymous credentials, and cryptographic promise.